Literacy and Skills' Role in Enhancing Handicraft SMEs' Performance and Reporting - Hamzah, Amir; Teti Rahmawati (Jurnal Manajemen, 2025)
This study aims to analyse the influence of financial, accounting, and digital literacy, bookkeeping skills, and financial report comprehension on the performance and financial reporting quality of SMEs. Using a quantitative approach and data analysis with SmartPLS, this research involves 130 respondents from small and medium-sized handicraft businesses in Kuningan Regency, Cirebon Regency, Cirebon City, Majalengka Regency, and Indramayu Regency. The results show that financial literacy and bookkeeping skills positively and significantly affect SME performance while accounting and digital literacy have no significant effect. All independent variables, such as financial, accounting, and digital literacy, bookkeeping skills, and financial report comprehension, significantly influence financial reporting quality. These findings suggest the importance of improving financial literacy and bookkeeping skills to enhance SMEs' performance and financial reporting quality and recommend that SME operators continue to strengthen these competencies to support their business success.